The effect of mark enhancement techniques on the presumptive and confirmatory tests for blood. Issue 6 (November 2018) - Stewart, Vanessa; Deacon, Paul; Zahra, Nathalie; Uchimoto, Mari L.; Farrugia, Kevin J.
Abstract: An investigation into the effects of physical and chemical enhancement on subsequent presumptive and confirmatory tests for human blood is presented. Human blood was deposited onto porous (white 80 gsm paper and brown envelope) and non-porous (tile and linoleum) substrates in a depletion series (30 depletions on non-porous and 20 on porous) and subjected to three ageing periods; 1, 7 and 28 days. A number of enhancement techniques were tested [fluorescence, black magnetic powder (BMP), iron-oxide black powder suspension (PS), cyanoacrylate (CA) fuming, acid violet 17 (AV17), acid yellow 7 (AY7), ninhydrin, DFO and Bluestar Forensic Magnum (BFM) luminol] to evaluate their potential effects on subsequent presumptive and confirmatory tests. AV17 and Bluestar provided the best enhancement and fully enhanced all depletions in the series. The sensitivity of the Kastle-Meyer (KM) (presumptive), Takayama and RSID-Blood tests (confirmatory) was initially investigated to determine the range of detectable depletions. The KM test detected all depletions, whereas the Takayama test detected up to depletion 6 and RSID-Blood detected up to depletion 20 (paper), 10 (envelope), 15 (tile) and 9 (lino). The abilities of these tests to detect blood after enhancement were then observed. A number of techniques resulted in little to no effect on any of the blood tests, whereas adverse effects were observed for others. Ninhydrin and CA fuming caused weak but instantaneous positive KM results whereas methanol-based AV17 and AY7 delayed the reaction by as much as 1 min. The Takayama test was not very sensitive, therefore, its performance was easily affected by enhancement and negative results were often observed. RSID-Blood tests were largely unaffected by chemical enhancement although a drop in positive results was observed for some of the techniques when compared to positive controls. Using a standard procedure for DNA extraction, all the tested blood samples (before and after enhancement) gave a detectable quantity of DNA and were successfully profiled. Out of the 45 samples processed for DNA profiling, 41 gave full profiles, while the remaining showed allele drop out in one or two loci. Highlights: Strategy to maximise evidence recovery (mark enhancement and blood) and efficiency. KM test considerably more sensitive than the Takayama and RSID tests. KM test largely unaffected by most enhancement techniques. Methanol-based protein stains affected the KM and Takayama tests but not the RSID test. DNA recovery from bloodstains was still possible after enhancement.